2021
DOI: 10.1158/1055-9965.epi-21-0871
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physical Activity Interventions among Rural Cancer Survivors: A Systematic Review and Meta-Analysis

Abstract: This review estimated the effectiveness of behavior change interventions to increase physical activity (PA) among rural adult cancer survivors. PubMed Medline, CINAHL, and PsychINFO were systematically searched through July 2020. Two independent investigators screened citations to identify studies to increase PA in adults residing in rural areas who had received any cancer diagnosis. Meta-analyses were conducted to assess proportion of participants achieving PA goal, paired mean difference (MD) in aerobic PA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…There have been very few PA interventions that have specifically recruited rural cancer survivors. Of the 5 RCTs included in Mama et al’s review, 21 none reported improvements in MVPA compared to controls. Limitations of previous studies in rural cancer survivors include intensive high-contact interventions (e.g., median intervention contact time was 467 min 21 ), the inclusion of metropolitan cancer survivors, 48 self-reported PA, and interventions focused on multiple health behaviors rather than PA alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been very few PA interventions that have specifically recruited rural cancer survivors. Of the 5 RCTs included in Mama et al’s review, 21 none reported improvements in MVPA compared to controls. Limitations of previous studies in rural cancer survivors include intensive high-contact interventions (e.g., median intervention contact time was 467 min 21 ), the inclusion of metropolitan cancer survivors, 48 self-reported PA, and interventions focused on multiple health behaviors rather than PA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5 RCTs included in Mama et al’s review, 21 none reported improvements in MVPA compared to controls. Limitations of previous studies in rural cancer survivors include intensive high-contact interventions (e.g., median intervention contact time was 467 min 21 ), the inclusion of metropolitan cancer survivors, 48 self-reported PA, and interventions focused on multiple health behaviors rather than PA alone. 23 This is an area in which scalable interventions are greatly needed to increase PA in under-served regional and remote cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than a quarter of studies have examined postintervention maintenance of PA in cancer survivors and, of those that have, just 22% of interventions were effective in promoting PA maintenance 5 . Research limited to PA maintenance in nonmetropolitan cancer survivors is scarce with no evidence for exercise maintenance at follow‐up in the handful of previous studies 6 . Relatively little is known about the effective maintenance of PA in cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the design of traditional PA interventions aimed at eliminating health disparities may reduce access for those cancer survivors who may stand to benefit the most (e.g., rural, functionally impaired/disabled) ( 10 ). The lack of accessible and effective home-based physical activity programs (HBPAP) for rural cancer survivors is a critically unmet need ( 17 ).…”
Section: Introductionmentioning
confidence: 99%